Silver coated porous silicon microarray SERS platform for detecting aflatoxin B1 fumonisin B1 and ochratoxin A - Rohit Kumar Singh; Narsingh R. Nirala; Sudharsan Sadhasivam; Divagar Muthukumar; Edward Sionov; Giorgi Shtenberg (npj Science of Food)
Abstract Toxigenic mold contamination in food and agricultural commodities affects a quarter of the world’s crops with massive economic losses and consequential health risks. Herein, we present a newly developed nanostructured microarray based on silver-coated porous silicon (Ag-pSi) used as a surface-enhanced Raman scattering (SERS) transducer. The internal porous void and pore morphology were optimized to amplify the SERS effect while achieving an enhancement factor of 1.75 × 107. The optimal structural features were used to analyze three target mycotoxins simultaneously using a portable Raman device. The optical output was inversely proportional to the analyte concentration upon selective biorecognition by the anti-target mycotoxin aptamer-modified scaffold. The Ag-pSi SERS substrate depicted low limits of detection (0.922, 0.547 and 0.008 ppb for ochratoxin A, fumonisin B1 and aflatoxin B1, respectively) within the range of 0.001-1000 ppb. Moreover, the selectivity, reusability, and overall shelf life were meticulously appraised while depicting satisfactory performance values (no interferences with competing mycotoxins, four regeneration cycles and three weeks of stability, respectively). Lastly, the developed SERS microarray was evaluated in different foodstuffs (wheat, maize and rice), with recovery values of 95–104% and RSD below 6.6%. The integrated approach offers a robust, field-deployable solution for a real-time multi-analyte screening platform for food and feed safety monitoring.